Effect of lanosterol on human cataract nucleus - P Mahesh Shanmugam; Aditya Barigali; Jayant Kadaskar; Sandip Borgohain; Divaynsh Kailash Chandra Mishra; Rajesh Ramanjulu; C K Minija (Indian Journal of Ophthalmology, 2015)
Aim: To study the effect of lanosterol on age-related cataractous human lens nuclei. Materials and Methods: Forty age-related cataractous nuclei removed during manual small incision cataract surgery were obtained and randomly immersed in 25 mM lanosterol solution or in control solution and stored at room temperature for 6 days. Pre- and post-immersion photographs were graded by two masked observers and collated for the regression or progression of lens opacity. Results: Both lanosterol and control groups showed progression or no change in the lens opacity at the end of 6 days. Conclusion: Lanosterol 25 mM solution did not reverse opacification of human age-related cataractous nuclei.